Improvement of peak-to-average power ratio reduction in orthogonal frequency - division multiplexing systems using free side information selected mapping method - Razavi, Sara (2014)
Digital band-pass modulation methods split in two groups, single carrier and multi carrier. A particular type of multi-carrier modulation is Orthogonal Frequency Division Multiplexing (OFDM) which is used in broadband wireless communication such as Worldwide Interoperability for Microwave Access (WiMAX), Long Term Evolution (LTE), and 4th Generation mobile telecommunications (4G). The OFDM system has many advantages over the FDM which is used in single carrier systems. One of the most significant advantages is signal protection against fading effects that happen through the nature of multipath environment. However OFDM signals suffer from a main drawback, which is high Peak to Average Power Ratio (PAPR). Passing high PAPR signal through the Power Amplifier (PA) causes distortions which make the PA operate beyond the linear area and enter to the saturation region. To solve the high PAPR problem in OFDM signals, various techniques have been developed such as Classical Selected Mapping (C-SLM) and Dummy Sequence Insertion (DSI). In the DSI method, by inserting the dummy signals the probability of PAPR is improved while the spectrum efficiency and data rate degrade. In the C-SLM method, the PAPR performance is enhanced at the expense of an increase in the number of Inverse Fast Fourier Transform (IFFT) which leads to higher complexity. Another disadvantage of the C-SLM method is named Side Information (SI) which is additional transmitted bits that assists the receiver to recover the original signal. Transmitting the SI bits decreases the bandwidth efficiency; moreover, when the receiver detects SI bits incorrectly, the entire received structure will be lost. In order to resist this trouble, strong channel coding should be used that protects the SI, but system complication and data rate reduction will appear as a result. In this thesis, a modified SLM scheme without Side Information is proposed which has the ability of transmitting and recovering the data signal without SI bits at a lower amount of computational complexity at the receiver side. Moreover in this method, some dummy sequences are inserted in order to better PAPR reduction. Regards to the simulation results the proposed method outperforms with 69% reduction in computational complexity at receiver side rather than the previous method. Furthermore the PAPR performances results illustrate around 3.8dB reduction, at CCDF 0.01 % or CCDF=10-4. The outcome of error performances in this method, demonstrate better BER performances at 16-QAM modulation.